Rater’s Intention Towards Appraising Accurately - MUHAMAD ALI EMBI; LOW KAH CHOON (Jurnal Studi Pemerintahan, 2014)
The aim of this article is to stimulate thoughts andintroduce new prospects to the study of performanceappraisal accuracy, especially in the raters’ perspective.It focuses on a relatively understudied aspectof performance appraisal which is raters’ intentiontowards appraising accurately. In order to understandthe application of this aspect, this paper attemptsto develop a conceptual framework basedon hypotheses of the direct and indirect factors thatpredict the raters’ intention to appraise accurately.It is hypothesized that the raters’ experience in appraising,raters’ perceived purposes of appraisal,and raters’ perceived information adequacy for appraisingwill predict the raters’ intention towardsappraising accurately by influencing the raters’ attitudetowards appraising accurately, raters’ perceivedsubjective norms towards appraising accurately, andraters’ perceived behavioral control towards appraisingaccurately.Keywords: performance appraisal accuracy, behavioralintentions, attitudes, perceived subjective norms,perceived behavioral control, background factors